Application of Pinch Analysis in an Integrated Steel Plant in Northern Sweden - Grip, Carl-Erik; Isaksson, Johan; Harvey, Simon; Nilsson, L. (ISIJ International, 2013)
The energy system in a modern integrated steel plant is a complicated network of units exchangingenergy and matter with each other. System studies using process integration tools are important to avoidsub-optimization. At the steel plant in Luleå such studies have been carried out using a MILP-based mathematicalprogramming tool (reMIND), mainly because of its inherent flexibility for handling combinedflows and reactions of both matter and chemical, thermal and mechanical energy. There are, however,areas where the energy system is dominated by creation, transport and exchange of thermal energy, andwhere pinch analysis can be expected to be a valuable tool. For this reason a pinch targeting study wascarried out for the plant site of the integrated steel plant in Luleå. The coke plant and the iron making/steelmaking plant were both studied with three ambition levels of possible improvements. The study confirmedthat pinch analysis is a powerful tool for targeting energy savings in areas where thermal energyflows dominate the local energy system, e.g., the gas cleaning area at the coke plant. The study also indicatedthat a connection between the energy systems in the coke plant and the iron making/steelmakingwould be valuable. This is not 100% feasible because of distance, but, a common steam net could add adegree of flexibility.